WEBSITE QUALITY, SOCIAL MEDIA AND SATISFACTION ON CHOOSING DECISIONS PRIVATE UNIVERSITIES - B, Mesra; Ferine, Kiki; Astuti, Desi; Sentosa, Ilham (TRIKONOMIKA, 2023)
This study aims to analyze the role of satisfaction in mediating the influence of website quality and social media on the decision to choose private universities in the city of Medan. The population in this study is all students enrolled in the Universitas Potensi Utama in 2022 while the sample of this study is 104 samples taken from 10% of the population. Data collection techniques using questionnaires and literature studies. Data processing with PLS smart program assistance tools. The results of this study show that the quality of websites and social media has a positive and significant effect on student satisfaction and students' decisions to choose the Universitas Potensi Utama. Other results indirectly show that the quality of websites and social media has a positive and significant effect on student decisions in choosing private universities through student satisfaction.